Pig design patterns : simplify Hadoop programming to create complex end-to-end enterprise big data solutions with Pig - Pasupuleti, Pradeep (Community experience distilled., 2014)
Pig makes Hadoop programming simple, intuitive, and fun to work with. It removes the complexity from Map Reduce programming by giving the programmer immense power through its flexibility. What used to be extremely lengthy and intricate code written in other high level languages can now be written in almost one tenth of the size using its easy to understand constructs. Pig has proven to be the easiest way to learn how to program Hadoop clusters, as evidenced by its widespread adoption. This comprehensive guide enables readers to readily use design patterns to simplify the creation of complex da.